Current Status of Research on Tuina for Analgesia: A Bibliometric and Visual Analysis - Wang Z; Xu H; Zhou H; Li W; Yang T; Zhou Y (Journal of Pain Research, 2023)
Zheng Wang,1,* Hui Xu,1,2,* Hang Zhou,1 Wanyu Li,1 Tao Yang,1 Yunfeng Zhou1 1Henan University of Chinese Medicine, Zhengzhou, 450046, People’s Republic of China; 2Tuina Department, the Third Affiliated Hospital of Henan University of Chinese Medicine, Zhengzhou, 450046, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yunfeng Zhou, College of Acupuncture and Massage, Henan University of Chinese Medicine, No. 156, Jinshui East Road, Zhengzhou, Henan Province, People’s Republic of China, Tel +8615639717497, Fax +86037165962633, Email zyf5680198@126.comPurpose: Tuina is a nonpharmacological modality for pain relief that has found applications in the treatment of several pain disorders. Tuina analgesia has been increasingly studied; however, few studies have focused on the previous publication trends, prevalent research areas, collaborations, and other factors. This study aimed to systematically analyze research trends and hot topics in the field of tuina analgesia over the past 30 years, using bibliometric analysis, to inform future research.Methods: The web of science database was searched for literature on tuina analgesia from 1992– 2023. VOSviewer and CiteSpace were used to analyze annual publication volumes, countries, institutions, journals and CO-cited journals, authorship, articles, and keywords and their relevance, and to perform co-occurrence and clustering analyses.Results: A total of 621 literature elements were included in the analysis. The annual volume of publications has increased steadily in recent years. The top three high-yielding countries were the United States, China, and Canada, respectively. The top three institutional outputs were from Shanghai University of Chinese medicine, Beijing University of Chinese medicine, and McMaster University, respectively. Notably, there was an imbalance between national outputs and centrality, with higher centrality in the United States (0.35) and lower in China (0.01). Cochrane Database of Systematic Reviews was the journal with the most publications (22), and PAIN was the most influential co-cited journals (publications=306). Moreover, current research in this field was dominated by studies on Tuina for relieving postoperative pain, the effectiveness of Tuina analgesia, and Tuina treatment for pain accompanied by anxiety.Conclusion: This study employed bibliometrics to analyze the literature on Tuina for pain treatment over a 30-year period, identifying potential collaborators, institutions, hot topics, and future research trends that will inform potential future directions.Keywords: analgesia, tuina, bibliometric analysis, VOSviewer, CiteSpace